Association of Intranasal and Neurogenic Dural Inflammation in Experimental Acute Rhinosinusitis - Lovrenčić, Luka; Matak, Ivica; Lacković, Zdravko (Frontiers in Pharmacology, 2020)
Background: Nasal cavity and sinus disorders, such as allergic rhinitis, rhinosinusitis, or certain anatomical defects, are often associated with transient or ongoing headaches. On the other hand, migraine headache patients often exhibit pain referral over the area of nasal sinuses and typical nasal autonomic symptoms involving congestion and rhinorrhea. Mechanism for convergence of nasal or sinus disorders and headaches is unknown. Herein, we examined the association of sino-nasal inflammatory pain with common preclinical indicators of trigeminovascular system activation such as dural neurogenic inflammation (DNI) and neuronal activation in brainstem nociceptive nuclei. Methods: Nasal and paranasal cavity inflammation and pain was induced by formalin (2.5%/10 μl) or capsaicin (0.1%/10 μl) instillation at the border of maxillary sinus and nasal cavity in rats. Quantification of inflammation of nasal mucosa and DNI was performed by spectrophotometric measurement of Evans blue - plasma protein complex extravasation. Pain behavior was quantified by rat grimace scale (RGS). Nociceptive neuronal activation in trigeminal nucleus caudalis (TNC) was assessed by c-Fos protein immunohistochemistry. Results: Capsaicin and formalin administered into rat nasal cavity increased plasma protein extravasation in the nasal mucosa and dura mater. Intensity of plasma protein extravasation in nasal mucosa correlated with extravasation in dura. Similarly, facial pain intensity correlated with nociceptive neuronal c-Fos activation in the TNC. Conclusion: Present data show that inflammatory stimuli in deep nasal and paranasal structures provoke distant intracranial changes related to trigeminovascular system activation. We hypothesize that this phenomenon could explain overlapping symptoms and comorbidity of nasal/paranasal inflammatory disorders with migraine.